Risk of renal cell carcinoma following exposure to metalworking fluids among autoworkers. Issue 10 (2nd August 2016) - Shrestha, Deepika; Liu, Sa; Hammond, S Katharine; LaValley, Michael P; Weiner, Daniel E; Eisen, Ellen A; Applebaum, Katie M
Abstract : Objectives: Metalworking fluids (MWF), used to cool and lubricate metal in occupational settings, are linked to several cancers but data on kidney cancer are limited. We examine how MWF influence the rate of renal cell carcinoma (RCC) in a large prospective study. Methods: A cohort of Michigan autoworkers consisting of 33 421 individuals was followed from 1985 to 2009. The cohort was linked to the Michigan Cancer Registry to identify new cases of RCC. We analysed RCC in relation to cumulative exposure to each specific type of MWF (straight, soluble and synthetic) and all 3 types pooled into a single MWF variable, with a 15-year lag. Cox proportional hazards regression with splines were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), controlling for age, gender, race, calendar year, year hired, time since hire, plant and other MWF types. Results: There were 135 incident cases. A linear increase in the log-HR was observed for RCC with increasing cumulative exposure to each MWF type and total MWF exposure. At the mean of total MWF exposure (18.80 mg/m 3 -year), the estimated HR was 1.11 (95% CI 1.04 to 1.19). Conclusions: Our results provide evidence for a dose-dependent association between MWF exposure and RCC. The influence of components of oil-based and water-based MWF needs further examination.